ANALISIS KELAYAKAN FINANSIAL JAMBU BIJI (Psidium guajava L.) VARIETAS KRISTAL - Astrini, Carmelita; Djuwendah, Endah; Karyani, Tuti; Wiyono, Sulistyodewi Nur (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
Guava Crystal variety currently has the high opportunity and potential to be developed in Indonesia. Waaida Farm as a company engaged in crystal guava farming in Sumedang District can only meet 5,71% of its demand every year. Therefore, Waaida Farm needs to expand the cultivation area to optimize the crystal guava potential. The expansion is constrained by lack of capital. Crystal guava farming in Waaida Farm is not bankable yet eventhough the business has run for six years. The objective of this research is to analyze financial feasibility of crystal guava farming at Waaida Farm. The research was conducted using qualitative descriptive design and case study technique. The data collection methods usedwere observation, interview and study literature. From the financial aspect, crystal guava farming at Waaida Farm is feasible to be implemented, based on the investment criteria using interest rate of 18,75%. The NPV is Rp 5.982.165, IRR is over the established interest rate of 28,43%, Net B/C is 1,59, and payback period is 5 years, shorter than the project term analysis of 10 years. The sensitivity analysis showed that decreasing inproduction is more sensitive than increasing inproduction cost. Nevertheless, the 10 percentchange of every variable still make the crystal guava farming feasible.